The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1678-4324-2016161056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preheating on Microstructure and Tensile Properties of Friction Stir Welded AA7075 Aluminium Alloy Joints

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…DOI: https://doi.org/10.11113/jm.v45.456 The beneficial effect of preheating on the A7075 aluminium alloy specimen was a successful weld joint for output in tensile strength and joint efficiency during process control [85]. Before welding a joint, add preheating process with a selection of the tool pin profile and the appropriate combination of parameters; it provides the presence of a microcavity that indicates ductility failure for joints [65].…”
Section: Mechanical Properties Of Dissimilar Fswmentioning
confidence: 99%
“…DOI: https://doi.org/10.11113/jm.v45.456 The beneficial effect of preheating on the A7075 aluminium alloy specimen was a successful weld joint for output in tensile strength and joint efficiency during process control [85]. Before welding a joint, add preheating process with a selection of the tool pin profile and the appropriate combination of parameters; it provides the presence of a microcavity that indicates ductility failure for joints [65].…”
Section: Mechanical Properties Of Dissimilar Fswmentioning
confidence: 99%
“…From Figure 2(a), the temperature in AS is much higher than that in RS, which indicates that the grains in AS may be much coarser than that in RS, resulting in different varying rate. When the preheating temperature is above 150°C, the temperature in the HAZ is close to peak ageing temperature [12], which was proved to enhance the precipitation hardening [5]. WNZ has the finest grains, owing to most of the grain boundaries, leading to highest microhardness.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It also reduces the frictional stress, shear stress, and stirring action. In the research of AA7075 Al alloy preheating FSW, the tensile strength of the joint and the welding efficiency under 100°C preheating were improved in comparison with that without preheating [5]. Preheating treatment improved the flow velocities of the plastic materials and reduced the influence of the difference between Al alloy and steel [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of studies on FSW performed during the determination of base material heat input through heat treatment is limited. In their study on the same topic, Poongkundran and Senthilkumar observed that tensile strength and joint impact improved if base metal is welded after it is heated up to 100 o C [17].…”
Section: Introductionmentioning
confidence: 96%